Bridging distances: Reflections on STEM education in Suriname’s interior - Collins, Jena M.; Short, Philip C.; McConnell III, John; Lee, Andrea Rakushin (American Journal of STEM Education, 2026)
This article shares reflections from a 2-week research trip to Suriname’s remote Sipaliwini District, where a U.S.-based research group engaged in conversations with teachers and administrators to discuss teaching and administrative experiences, STEM education integration, challenges of teaching in remote areas, and recommendations for policy and practice. The article includes background information on the education system of Suriname and some of the predominant challenges faced in remote schools within the interior of the country. This article is a reflective scholarly account drawing on field experiences. It highlights issues related to access, infrastructure, and educational equity in interior communities of Suriname.